Catalytic effect of polyethylene glycol on sulfur oxidation in chalcopyrite bioleaching by Acidithiobacillus ferrooxidans. (September 2016) - Zhang, Ruiyang; Wei, Dezhou; Shen, Yanbai; Liu, Wengang; Lu, Tao; Han, Cong
Highlights: Sulfur oxidation activity of A. ferrooxidans was promoted by PEG addition. The passivation of chalcopyrite surface was caused by S 0 and jarosite. S 0 deposited on the mineral surface was eliminated by the addition of PEG. Cu extraction yield from chalcopyrite was increased by 1.19 times by PEG addition. Abstract: Polyethylene glycol (PEG) was used as a catalyst to enhance chalcopyrite bioleaching with Acidithiobacillus ferrooxidans in shake flasks. The effects of PEG on the sulfur oxidation of A. ferrooxidans and on the process of chalcopyrite bioleaching were investigated. The morphology, main components and sulfur speciation of bioleached chalcopyrite surfaces were evaluated combining with XRD, SEM and XPS. It was demonstrated that addition of PEG could significantly improve the bioleaching of chalcopyrite. Furthermore, the results indicated that elemental sulfur and jarosite were the main components of the passivation layer during the bioleaching of chalcopyrite. PEG could promote the sulfur oxidation by A. ferrooxidans due to an increase in bacterial attachment, and therefore accelerate the biooxidation of elemental sulfur generated in leaching process. It was found that PEG eliminated inhibitory elemental sulfur from the chalcopyrite surface which could be the main reason for enhanced the leaching efficiency.